2010
DOI: 10.1002/lary.21043
|View full text |Cite
|
Sign up to set email alerts
|

Posterior hyoid space as related to excision of the thyroglossal duct cyst

Abstract: The technique of applying the concept of a PHS to ensure the complete resection of the middle third of the hyoid bone and offending tissues is believed to decrease recurrence of TGDC secondary to incomplete resection in the perihyoid area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 11 publications
2
27
0
1
Order By: Relevance
“…This study represents the largest histologic series in children to determine this, including cases of both primary and revision procedures. These results reaffirm that to minimize persistence following a primary procedure, tissue superior to the hyoid bone should be removed routinely—even if no gross disease is noted at the time of surgery, as initially described by Sistrunk and confirmed by Maddalozzo et al…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…This study represents the largest histologic series in children to determine this, including cases of both primary and revision procedures. These results reaffirm that to minimize persistence following a primary procedure, tissue superior to the hyoid bone should be removed routinely—even if no gross disease is noted at the time of surgery, as initially described by Sistrunk and confirmed by Maddalozzo et al…”
Section: Discussionsupporting
confidence: 65%
“…Persistent disease following a primary procedure to excise a TGDC is frustrating to both the surgeon and the patient and their parent/guardian, who must now entertain a second general anesthetic and a second, more extensive surgical procedure, not to mention the increased healthcare costs to treat this disease. Maddalozzo et al have proposed that persistence is due to either incomplete resection of the hyoid bone and/or the presence of multiple microscopic tracts in the suprahyoid region . Others have suggested that the infrahyoid area is a site of persistent disease .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Habitualmente, la PCT se presenta como una tumoración en el área perihioidea (98%), 5 renitente, adherida a planos superficiales, que asciende con la deglución, y el diagnóstico es fundamentalmente clínico. Otra forma de presentación es un orificio en la línea media, a través del cual puede salir material mucoso.…”
Section: Discussionunclassified